Hemodynamic changes in ALPPS influence liver regeneration and function: results from a prospective study. Issue 5 (May 2019) - Tomassini, Federico; D'Asseler, Yves; Giglio, Mariano C.; Lecluyse, Clarisse; Lambert, Bieke; Sainz-Barriga, Mauricio; Van Dorpe, Jo; Hoorens, Anne; Geboes, Karen; Troisi, Roberto I.
Abstract: Background: Excessive increase of portal flow and pressure following extended hepatectomy have been associated to insufficient growth or function of the future liver remnant (FLR), with the risk of post-hepatectomy liver failure (PHLF). We prospectively assess the influence of liver hemodynamics on FLR regeneration and function in Associating Liver Partition and Portal vein ligation for Staged hepatectomy (ALPPS). Methods: Twenty-three patients underwent ALPPS; liver hemodynamics were assessed throughout the procedures. Volume and function of the FLR were evaluated by angio-CT and 99mTc-Mebrofenin-scintigraphy. Results: The portal vein flow at the end of stage-1 correlated with the increase of the FLR volume (p = 0.002). Patients with portal vein pressure (PVP) < 20 mmHg and hepatic to portal vein gradients (HVPG) < 15 mmHg at the end of ALPPS-1 showed higher FLR regeneration (76.7% vs. 30.6%, p = 0.04) and function (26.7% vs. −0.13%, p = 0.02). FLR regeneration was inversely correlated with baseline FLR/Total Liver Volume (p = 0.002) and FLR/Body Weight (p = 0.02). No correlation was found between volumes and function (p = 0.13). Conclusion: Liver hemodynamic stress at the end of ALPPS-1 influences the increase of the FLR volume and function, which is higher with PVP < 20 and HVPG < 15 mmHg. Liver volume overestimates liver function and could be imprecise to set stage-2 timing.